Population dynamics of small towns, which received city status during independence of Ukraine - Мельник, Людмила; Кривець, Ольга; Батиченко, Світлана (Human Geography Journal, 2017)
The rise of population quantity of the city  is the key factor development. The rise or down of population quantity of the city  is an indicator of the settlement  development or decline. Small towns, established in the period ofUkraine  independence are actual objects of social-geographical research. To the category Small towns inUkraineare included the towns with a population of 50 thousand inhabitants. The preconditions of getting the town status were analyzed. as a result  We got next groups of towns:  historical-cultural towns which lost the city status during the Soviet period; historical and cultural towns, which first received city status  in  independentUkraine; settlements created during the Soviet era which had a special purpose (military); based settlements during the Soviet era as a center of energetic industry sector. These settlements got the town status  in three periods: in the early 90's, the late 90's, the modern period. According to population quantity of towns the grouping was conducted. The following  groups are identified: up to 5 thousand residents (three cities), 5-10 thousand residents (six cities) 10-20 thousand population (10 cities), 20-50 thousand residents (three cities). More than a half of the cities  are characterised by the population decline. Two cites  -Pereshchepino and Svetlodarsk are characterized by stable changes in population dynamics indicators . Population growth is typical for Kyiv's satellites (Bucha) andOdessa's (Yuzhny, Teplodar), as well as for military cities.